2018
DOI: 10.1002/ece3.4365
|View full text |Cite
|
Sign up to set email alerts
|

Multiannual effects of induced plant defenses: Are defended plants good or bad neighbors?

Abstract: Defenses induced by herbivore feeding or phytohormones such as methyl jasmonate (MeJA) can affect growth, reproduction, and herbivory, not only on the affected individual but also in its neighboring plants. Here, we report multiannual defense, growth, and reproductive responses of MeJA‐treated bilberry (Vaccinium myrtillus) and neighboring ramets. In a boreal forest in western Norway, we treated bilberry ramets with MeJA and water (control) and measured responses over three consecutive years. We observed the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 75 publications
(104 reference statements)
4
30
0
Order By: Relevance
“…Our results suggest that bilberry plants are more responsive to induced defenses in the suboptimal lower elevation, where the average temperature is higher and the timing of snow melt is earlier, by allocating resources from growth and reproduction to effective herbivory defense for at least one year after induction. This result corroborates with our previous ecological study showing that the induced defense system in low‐land bilberry plants functions in a multiannual manner (Benevenuto et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results suggest that bilberry plants are more responsive to induced defenses in the suboptimal lower elevation, where the average temperature is higher and the timing of snow melt is earlier, by allocating resources from growth and reproduction to effective herbivory defense for at least one year after induction. This result corroborates with our previous ecological study showing that the induced defense system in low‐land bilberry plants functions in a multiannual manner (Benevenuto et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The plant is considered as a key food source for herbivores, pollinators, and fruit eating birds and mammals in northern European boreal forest ecosystems (Hegland et al, ; Hjältén, Danell, & Ericson, ; Jacquemart, ; Selas, ), and has been found to be sensitive to environmental changes. In previous studies, we showed that defenses induced by herbivore feeding or treatment with MeJA reduce herbivory and increase reproduction of the damaged or treated plants (Benevenuto et al, ; Hegland, Seldal, Lilleeng, & Rydgren, ; Seldal, Hegland, Rydgren, Rodriguez‐Saona, & Töpper, ). These studies provide evidence of potential trade‐offs between growth and defense in bilberry plants when coping with herbivore attack.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations